Method for preparing hydrogel film on non-conductive surface
By using a nanodialysis membrane to separate the electrode space in an electrodeposition cell, electrophoretic deposition of polyelectrolytes on the surface of a non-conductive substrate is achieved. This solves the problem of preparing hydrogel films on non-conductive substrates in traditional methods and provides a rapid and stable method for preparing hydrogel films, which is applicable to a variety of polyelectrolyte materials.
Patent Information
- Application Number
- CN202511077132.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-01
- Publication Date
- 2025-11-28
AI Technical Summary
Existing technologies struggle to efficiently prepare hydrogel films on non-conductive substrates, and traditional methods rely on conductive electrodes and chemical additives, resulting in poor interfacial adhesion, uneven structure, and limited applicability.
A nanodialysis membrane is used to separate the electrode space in an electrodeposition cell. Polyelectrolytes and salting-out ion solutions are injected separately. Under the action of an electric field, the polyelectrolytes are directionally migrated and electrophoretically deposited to form a hydrogel film.
Achieve rapid and stable construction of hydrogel films on non-conductive substrates, exhibiting good uniformity and mechanical properties. Applicable to a variety of polyelectrolyte materials, the process is simple, environmentally friendly and non-toxic, and suitable for flexible devices and biomaterial surfaces.
Smart Images

Figure CN121021880A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of biomaterial preparation technology, and more specifically to a method for preparing hydrogel films on non-conductive surfaces. Background Technology
[0002] Polyelectrolyte hydrogels, due to their unique physicochemical properties such as good biocompatibility, stimulus responsiveness, high water content, and tunable mechanical properties, have shown broad application prospects in fields such as tissue engineering, drug delivery, biosensors, and flexible electronic devices. In particular, the fabrication technology of hydrogel films has become a research hotspot in the construction of biomimetic materials and interfacial functional layers.
[0003] The main methods for constructing hydrogel films include drop coating, spin coating, spray coating, molding, and electrodeposition. Among these, electrodeposition technology is widely used for the deposition of polyelectrolyte hydrogels due to its controllable process, strong spatial selectivity, and suitability for preparing complex structures. For example, inducing the deposition of polyelectrolytes such as chitosan, gelatin, and sodium alginate on the electrode interface using a DC or AC electric field has become a mature method. However, these methods typically rely on metal or carbon-based conductive substrates, such as platinum sheets, electrode cores, and ITO glass, which limits material selection and makes it difficult to achieve hydrogel deposition on non-conductive materials such as polymer films, flexible substrates, or biological interfaces, severely restricting its applicability in practical applications. Furthermore, due to the high reactivity of conductive substrate electrode surfaces, problems such as bubble formation and accumulation of electrolysis byproducts often occur, leading to poor interfacial adhesion, poor structural uniformity, and even defects such as peeling and delamination in the prepared hydrogel films, affecting their mechanical properties and functional stability. Some studies have attempted to improve adhesion by pretreating the substrate surface or introducing coupling agents, but this undoubtedly increases process complexity and reduces preparation efficiency and scalability.
[0004] Currently, some existing technologies have attempted to utilize electric fields to induce structural changes in protein molecules to form hydrogel membranes. For example, patent CN103981561A discloses a method for inducing the formation of a hydrogel membrane from a solution containing silk fibroin through a barrier membrane under the action of an electric field. This method introduces Tris-glycine buffer and SDS into an inner and outer dual-cavity electrolysis device, and promotes the formation of a hydrogel membrane from silk fibroin on the surface of a nanoporous barrier membrane by applying an external direct current. Although this method achieves the gelation of silk fibroin on the surface of non-conductive materials, it still has the following shortcomings: 1) The electrolyte composition is complex; 2) The core mechanism of this method relies on SDS-induced self-assembly into a membrane. SDS poses a biotoxicity risk, and the residue is not easy to completely remove, making it difficult to use in cell contact medical scenarios; 3) This method is applicable to protein systems and lacks compatibility with other polyelectrolyte materials.
[0005] To overcome the problems of complex equipment, reliance on chemical additives, uncontrollable structure, and limited applicability of existing electric field-induced hydrogel preparation methods, this invention provides a novel strategy based on the directional migration of soluble salt ions to induce polyelectrolyte electrophoretic deposition. Summary of the Invention
[0006] To address the shortcomings of existing technologies, this invention provides a method for forming polyelectrolyte hydrogel films on non-conductive substrates without relying on electrode interfaces. This method involves setting a nanodialysis membrane in an electrodeposition cell to separate the electrode space, and injecting a polyelectrolyte solution and a salting-out ion solution into the anolyte and cathode cells, respectively. Under the influence of an electric field, a stable ion concentration gradient and polyelectrolyte migration behavior are formed, thereby driving electrophoretic deposition and structural reorganization of the polyelectrolyte on one side of the dialysis membrane, achieving the construction of an asymmetric hydrogel. This solves the problems of existing electric field-induced hydrogel preparation methods, such as complex equipment, reliance on chemical additives for induction mechanisms, uncontrollable structure, and limited applicability to specific systems.
[0007] To achieve the above objectives, the specific technical solution of the present invention is as follows:
[0008] This invention provides a method for preparing a hydrogel film on a non-conductive surface, comprising the following steps:
[0009] Step 1: Construct an electrodeposition cell system including a cathode cell and an anode cell, and place a hydrophilic non-conductive substrate between the cathode cell and the anode cell as a deposition carrier for the hydrogel film.
[0010] Step 2: Inject the aqueous solution containing polyelectrolytes into the anode tank and inject the aqueous solution containing soluble salts into the cathode tank.
[0011] Step 3: Apply a DC electric field between the cathode and the anode to cause the positively charged polyelectrolyte molecules in the anode cell to undergo electrophoretic migration and accumulate near the non-conductive substrate interface to form a hydrogel film.
[0012] Step 4: Remove the hydrogel film, clean it to remove residual ions and unreacted substances, and obtain the target polyelectrolyte hydrogel film.
[0013] The principle of this invention is as follows: This invention utilizes an electric field to drive the directional migration of polyelectrolyte molecules, achieving local aggregation and in-situ formation of a hydrogel film on the surface of a non-conductive, hydrophilic substrate. By controlling the direction of the electric field, ion distribution, and reaction conditions, a hydrogel layer can be constructed on a neutral or flexible substrate without relying on conductive electrodes and chemical additives, offering advantages of ease of operation and strong applicability. The non-conductive substrate used in this invention is a key component connecting the cathode and anode cells in the electrodeposition cell. The non-conductive substrate is a non-conductive nanoporous membrane, selected from polyvinylidene fluoride (PVDF) membranes, polyamide (PA) membranes, or cellulose acetate (CA) membranes, etc., possessing excellent mechanical strength and chemical resistance. Its pore size ranges from 1 nm to 100 nm, preferably from 10 nm to 50 nm. The membrane length ranges from 5 cm to 50 cm, the width ranges from 5 cm to 30 cm, and the thickness ranges from 10 µm to 500 µm, which can be flexibly adjusted according to the size of the electrodeposition cell. The non-conductive substrate is fixed between the cathode and anode cells by clamping to ensure its flatness and liquid isolation. Under the action of an electric field, the hydrogel is deposited and formed in situ on the surface of the non-conductive substrate by adjusting the electric field strength, electrolyte pH, salt concentration and reaction time.
[0014] Further, in step 1, the non-conductive substrate includes, but is not limited to, one or more of polyvinylidene fluoride (PVDF) film, polyamide (PA) film, cellulose acetate (CA) film, glass sheet, polyester film, and polypropylene film. Further, in step 1, the electrodeposition cell is made of, but is not limited to, one or more of glass, plastic, and ceramic.
[0015] Furthermore, the plastic includes, but is not limited to, one or more of polytetrafluoroethylene, polypropylene, polyethylene, and polyvinyl chloride.
[0016] Furthermore, the electrodeposition cell of the present invention can be rectangular or other arbitrary shapes, and its internal dimensions can be designed according to actual needs. When the electrodeposition cell is rectangular, its dimensions are preferably: length 5 cm to 20 cm, width 3 cm to 15 cm, and height 4 cm to 25 cm. In a specific example of the present invention, the laboratory-scale electrodeposition cell has dimensions of 5 cm long × 3 cm wide × 4 cm high, with a volume of approximately 60 mL; the pilot-scale electrodeposition cell has dimensions of 15 cm long × 10 cm wide × 20 cm high, with a volume of approximately 3 L. The above dimensions are preferred embodiments, and those skilled in the art can adjust the dimensions of the electrodeposition cell according to actual needs without departing from the protection scope of the present invention.
[0017] Furthermore, in step 2, the mass concentration of the polyelectrolyte in the aqueous solution containing the polyelectrolyte is 0.5wt%-10wt%.
[0018] Furthermore, in step 2, the polyelectrolyte includes, but is not limited to, one or more of chitosan, gelatin, and sodium alginate.
[0019] Furthermore, in step 2, the molar concentration of the soluble salt in the aqueous solution containing the soluble salt is 0.001-1.5 mol / L.
[0020] Furthermore, in step 2, the soluble salt includes, but is not limited to, sodium chloride and / or sodium citrate.
[0021] Furthermore, in step 3, the distance between the cathode and the anode is 1-20 cm.
[0022] Furthermore, in step 3, the intensity of the DC electric field is 1-10 V / cm.
[0023] The present invention also provides an electrodeposition apparatus for implementing the method, comprising a cathode cell, an anode cell, and a non-conductive substrate. The anode cell is used to hold an aqueous solution containing a polyelectrolyte and is provided with an anode. The cathode cell is used to hold an aqueous solution containing a soluble salt and is provided with a cathode. The non-conductive substrate is fixed between the cathode cell and the anode cell to ensure its flatness and liquid isolation. By applying a DC electric field between the cathode and the anode, a hydrogel film can be formed at the interface of the non-conductive substrate.
[0024] Compared with the prior art, the advantages of the present invention are:
[0025] 1. This invention introduces a hydrophilic, non-conductive substrate into an electrolytic cell, and applies solutions of different compositions and electric fields to both sides of the substrate. It fully utilizes the electrophoretic migration characteristics of polyelectrolytes under the influence of an electric field, causing them to accumulate and cross-link near the non-conductive substrate, ultimately forming a continuous and stable hydrogel film. Even with a deposition time of only 1 minute, the resulting film still exhibits good uniformity; and even with a deposition time of only 10 minutes, the resulting film still displays excellent mechanical properties. This invention overcomes the limitation of traditional electrodeposition techniques that rely on conductive substrates, providing a universal platform for constructing functional hydrogels on the surfaces of non-conductive materials such as glass and polymer films.
[0026] 2. Compared with existing technologies, the method of this invention does not rely on conductive electrodes and chemically inducing additives. The materials or reagents involved are inexpensive and non-toxic. The entire system is green, environmentally friendly, and highly biocompatible. It has strong structural tunability, and different thicknesses, densities, and functional gradients can be controlled by programming electric field parameters, ion types, and concentrations. It has wide applicability and is suitable for natural / synthetic polyelectrolyte molecules such as gelatin, chitosan, collagen, polyacrylamide, sodium alginate, and nanocellulose. It is fast to prepare, uses simple equipment, operates under mild conditions, is easy to scale up industrially, does not rely on complex devices and special electrode systems, and is suitable for various applications such as flexible devices and biomaterial surfaces. It has great application potential in the field of biomimetic material preparation. Attached Figure Description
[0027] Figure 1 This is a schematic diagram of the electrodeposition apparatus of the present invention. In the diagram, 1 is the power source, 2 is the anode, 3 is the cathode, 4 is the non-conductive substrate, 5 is the anode cell, and 6 is the cathode cell.
[0028] Figure 2 Images of chitosan hydrogel membranes prepared at different deposition times in Examples 1-6;
[0029] Figure 3 The graph shows the relationship between different deposition times and chitosan hydrogel film thickness in Examples 1-7;
[0030] Figure 4 This is a cross-sectional electron microscope image of the chitosan hydrogel film deposited for 1 minute in Example 1;
[0031] Figure 5 The graphs show the mechanical properties of chitosan hydrogel films at different deposition times in Examples 4-7.
[0032] Figure 6 The mechanical properties of the gelatin hydrogel films prepared in Example 8 and Comparative Example 1 are shown in the figure. Detailed Implementation
[0033] The technical solution of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0034] This invention provides a method for preparing a hydrogel film on a non-conductive surface, comprising the following steps:
[0035] Step 1: Construct an electrodeposition cell system including a cathode cell and an anode cell, and place a hydrophilic non-conductive substrate between the cathode cell and the anode cell as a deposition carrier for the hydrogel film.
[0036] Step 2: Inject the aqueous solution containing polyelectrolytes into the anode tank and inject the aqueous solution containing soluble salts into the cathode tank.
[0037] Step 3: Apply a DC electric field between the cathode and the anode to cause the positively charged polyelectrolyte molecules in the anode cell to undergo electrophoretic migration and accumulate near the non-conductive substrate interface to form a hydrogel film.
[0038] Step 4: Remove the hydrogel film, clean it to remove residual ions and unreacted substances, and obtain the target polyelectrolyte hydrogel film.
[0039] In some examples, the non-conductive substrate is a non-conductive nanoporous membrane with a pore size of 1-100 nm and a thickness of 10-500 µm. In the following specific embodiments, unless otherwise specified, the non-conductive substrate is a 30 µm thick nanodialysis membrane with a permeable molecular weight of 1000 Da (corresponding to a pore size of 1 nm).
[0040] In some examples, the non-conductive substrate includes, but is not limited to, one or more of polyvinylidene fluoride (PVDF) membranes, polyamide (PA) membranes, cellulose acetate (CA) membranes, glass sheets, polyester films, and polypropylene membranes; the electrodeposition cell is made of, but is not limited to, one or more of glass, plastics, and ceramics, and the plastics include, but are not limited to, one or more of polytetrafluoroethylene, polypropylene, polyethylene, and polyvinyl chloride.
[0041] In some examples, the electrodeposition cell is rectangular or other arbitrary shapes, and its internal dimensions can be designed according to actual needs. When the electrodeposition cell is rectangular, its dimensions are: length 5-20 cm, width 3-15 cm, and height 4-25 cm.
[0042] In some examples, the mass concentration of the polyelectrolyte in the aqueous solution containing the polyelectrolyte is 0.5 wt%-10 wt%; and the molar concentration of the soluble salt in the aqueous solution containing the soluble salt is 0.001-1.5 mol / L.
[0043] In some examples, the polyelectrolyte includes, but is not limited to, one or more of chitosan, gelatin, and sodium alginate; the soluble salt includes, but is not limited to, sodium chloride and / or sodium citrate.
[0044] In some examples, the distance between the cathode and the anode is 1-20 cm.
[0045] In some examples, the intensity of the DC electric field is 1-10 V / cm.
[0046] The present invention also provides an electrodeposition apparatus for implementing the method, comprising a cathode cell, an anode cell, and a non-conductive substrate. The anode cell is used to hold an aqueous solution containing a polyelectrolyte and is provided with an anode. The cathode cell is used to hold an aqueous solution containing a soluble salt and is provided with a cathode. The non-conductive substrate is fixed between the cathode cell and the anode cell to ensure its flatness and liquid isolation. By applying a DC electric field between the cathode and the anode, a hydrogel film can be formed at the interface of the non-conductive substrate.
[0047] Example 1
[0048] A method for preparing a hydrogel film on a non-conductive surface includes the following steps:
[0049] Dissolve 1 g of chitosan powder in deionized water, add an appropriate amount of hydrochloric acid to adjust the pH to 4-5, and stir at room temperature for 12 h to completely dissolve the chitosan, obtaining a 1 wt% chitosan solution. Dissolve 10 g of trisodium citrate dihydrate powder in deionized water, stir at room temperature for 2 h to obtain a 10 wt% sodium citrate aqueous solution, and degas by sonication for 15 min. Prepare a platinum sheet with a length of 6 cm, a width of 2 cm, and a thickness of 1 mm as the anode material and a titanium sheet with a length of 6 cm, a width of 2 cm, and a thickness of 1 mm as the cathode material, which will serve as the anode and cathode for electrophoretic deposition, respectively. Install the anode and cathode cells and sandwich a nanodialysis membrane between the two cells. Immerse the anode and cathode metal materials in the anode cell containing the chitosan solution and the cathode cell containing the sodium citrate solution, with an insertion depth of 5 cm and a spacing of 4 cm. Apply a constant voltage DC current between the anode and cathode, with an electric field strength of 4 V / cm, and perform electrophoretic deposition of chitosan for 1 min (see actual image). Figure 2 After deposition, the hydrogel film was removed from the nanodialysis membrane and washed to remove residual ions and unreacted substances, yielding a continuous and stable layered chitosan hydrogel film with a thickness of 150 μm (the relationship between deposition time and hydrogel film thickness is shown in...). Figure 3 The cross-sectional structure of the thin film is shown in [reference needed]. Figure 4 ).Depend on Figure 4 It can be seen that even with a deposition time of only 1 minute, the generated film still has good uniformity.
[0050] Example 2
[0051] A method for preparing a hydrogel film on a non-conductive surface includes the following steps:
[0052] Dissolve 1 g of chitosan powder in deionized water, add an appropriate amount of hydrochloric acid to adjust the pH to 4-5, and stir at room temperature for 12 h to completely dissolve the chitosan, obtaining a 1 wt% chitosan solution. Dissolve 10 g of trisodium citrate dihydrate powder in deionized water, stir at room temperature for 2 h to obtain a 10 wt% sodium citrate aqueous solution, and degas by sonication for 15 min. Prepare a platinum sheet with a length of 6 cm, a width of 2 cm, and a thickness of 1 mm as the anode material and a titanium sheet with a length of 6 cm, a width of 2 cm, and a thickness of 1 mm as the cathode material, which will serve as the anode and cathode for electrophoretic deposition, respectively. Install the anode and cathode cells and sandwich a nanodialysis membrane between the two cells. Immerse the anode and cathode metal materials in the anode cell containing the chitosan solution and the cathode cell containing the sodium citrate solution, with an insertion depth of 5 cm and a spacing of 4 cm. Apply a constant voltage DC current with an electric field strength of 4 V / cm to perform electrophoretic deposition of chitosan for 3 min (see actual image). Figure 2 After deposition, the hydrogel film was removed from the nanodialysis membrane, washed to remove residual ions and unreacted substances, yielding a chitosan hydrogel film with a thickness of 180 μm (the relationship between deposition time and hydrogel film thickness is shown in [reference]). Figure 3 ).
[0053] Example 3
[0054] A method for preparing a hydrogel film on a non-conductive surface includes the following steps:
[0055] Dissolve 1 g of chitosan powder in deionized water, add an appropriate amount of hydrochloric acid to adjust the pH to 4-5, and stir at room temperature for 12 h to completely dissolve the chitosan, obtaining a 1 wt% chitosan solution. Dissolve 10 g of trisodium citrate dihydrate powder in deionized water, stir at room temperature for 2 h to obtain a 10 wt% sodium citrate aqueous solution, and degas by sonication for 15 min. Prepare a platinum sheet with a length of 6 cm, a width of 2 cm, and a thickness of 1 mm as the anode material and a titanium sheet with a length of 6 cm, a width of 2 cm, and a thickness of 1 mm as the cathode material, which will serve as the anode and cathode for electrophoretic deposition, respectively. Install the anode and cathode cells and sandwich a nanodialysis membrane between the two cells. Immerse the anode and cathode metal materials in the anode cell containing the chitosan solution and the cathode cell containing the sodium citrate solution, with an insertion depth of 5 cm and a spacing of 4 cm. Apply a constant voltage DC current with an electric field strength of 4 V / cm to perform electrophoretic deposition of chitosan for 5 min (see actual image). Figure 2 After deposition, the hydrogel film was removed from the nanodialysis membrane and washed to remove residual ions and unreacted substances, yielding a 220 μm thick chitosan hydrogel film (the relationship between deposition time and hydrogel film thickness is shown in [reference]). Figure 3 ).
[0056] Example 4
[0057] A method for preparing a hydrogel film on a non-conductive surface includes the following steps:
[0058] Dissolve 1 g of chitosan powder in deionized water, add an appropriate amount of hydrochloric acid to adjust the pH to 4-5, and stir at room temperature for 12 h to completely dissolve the chitosan, obtaining a 1 wt% chitosan solution. Dissolve 10 g of trisodium citrate dihydrate powder in deionized water, stir at room temperature for 2 h to obtain a 10 wt% sodium citrate aqueous solution, and degas by sonication for 15 min. Prepare a platinum sheet with a length of 6 cm, a width of 2 cm, and a thickness of 1 mm as the anode material and a titanium sheet with a length of 6 cm, a width of 2 cm, and a thickness of 1 mm as the cathode material, which will serve as the anode and cathode for electrophoretic deposition, respectively. Install the anode and cathode cells and sandwich a nanodialysis membrane between the two cells. Immerse the anode and cathode metal materials in the anode cell containing the chitosan solution and the cathode cell containing the sodium citrate solution, with an insertion depth of 5 cm and a spacing of 4 cm. Apply a constant voltage DC current with an electric field strength of 4 V / cm to perform electrophoretic deposition of chitosan for 10 min (see actual image). Figure 2 After deposition, the hydrogel film was removed from the nanodialysis membrane and washed to remove residual ions and unreacted substances, yielding a 320 μm thick chitosan hydrogel film (the relationship between deposition time and hydrogel film thickness is shown in...). Figure 3 The mechanical properties of the thin film are shown in Figure 5 ).Depend on Figure 5 It can be seen that even with a deposition time of only 10 minutes, the resulting film still exhibits good mechanical properties.
[0059] Example 5
[0060] A method for preparing a hydrogel film on a non-conductive surface includes the following steps:
[0061] Dissolve 1 g of chitosan powder in deionized water, add an appropriate amount of hydrochloric acid to adjust the pH to 4-5, and stir at room temperature for 12 h to completely dissolve the chitosan, obtaining a 1 wt% chitosan solution. Dissolve 10 g of trisodium citrate dihydrate powder in deionized water, stir at room temperature for 2 h to obtain a 10 wt% sodium citrate aqueous solution, and degas by sonication for 15 min. Prepare a platinum sheet with a length of 6 cm, a width of 2 cm, and a thickness of 1 mm as the anode material and a titanium sheet with a length of 6 cm, a width of 2 cm, and a thickness of 1 mm as the cathode material, which will serve as the anode and cathode for electrophoretic deposition, respectively. Install the anode and cathode cells and sandwich a nanodialysis membrane between the two cells. Immerse the anode and cathode metal materials in the anode cell containing the chitosan solution and the cathode cell containing the sodium citrate solution, with an insertion depth of 5 cm and a spacing of 4 cm. Apply a constant voltage DC current with an electric field strength of 4 V / cm to perform electrophoretic deposition of chitosan for 30 min (see actual image). Figure 2After deposition, the hydrogel film was removed from the nanodialysis membrane, washed to remove residual ions and unreacted substances, yielding a 530 μm thick chitosan hydrogel film (the relationship between deposition time and hydrogel film thickness is shown in...). Figure 3 The mechanical properties of the thin film are shown in Figure 5 ).
[0062] Example 6
[0063] A method for preparing a hydrogel film on a non-conductive surface includes the following steps:
[0064] Dissolve 1 g of chitosan powder in deionized water, add an appropriate amount of hydrochloric acid to adjust the pH to 4-5, and stir at room temperature for 12 h to completely dissolve the chitosan, obtaining a 1 wt% chitosan solution. Dissolve 10 g of trisodium citrate dihydrate powder in deionized water, stir at room temperature for 2 h to obtain a 10 wt% sodium citrate aqueous solution, and degas by sonication for 15 min. Prepare a platinum sheet with a length of 6 cm, a width of 2 cm, and a thickness of 1 mm as the anode material and a titanium sheet with a length of 6 cm, a width of 2 cm, and a thickness of 1 mm as the cathode material, which will serve as the anode and cathode for electrophoretic deposition, respectively. Install the anode and cathode cells and sandwich a nanodialysis membrane between the two cells. Immerse the anode and cathode metal materials in the anode cell containing the chitosan solution and the cathode cell containing the sodium citrate solution, with an insertion depth of 5 cm and a spacing of 4 cm. Apply a constant voltage DC current with an electric field strength of 4 V / cm to perform electrophoretic deposition of chitosan for 60 min (see actual image). Figure 2 After deposition, the hydrogel film was removed from the nanodialysis membrane and washed to remove residual ions and unreacted substances, yielding a chitosan hydrogel film with a thickness of 690 μm (the relationship between deposition time and hydrogel film thickness is shown in [reference]). Figure 3 The mechanical properties of the thin film are shown in Figure 5 ).
[0065] Example 7
[0066] A method for preparing a hydrogel film on a non-conductive surface includes the following steps:
[0067] 1 g of chitosan powder was dissolved in deionized water, and an appropriate amount of hydrochloric acid was added to adjust the pH to 4-5. The mixture was stirred at room temperature for 12 h to completely dissolve the chitosan, yielding a 1 wt% chitosan solution. 10 g of trisodium citrate dihydrate powder was dissolved in deionized water and stirred at room temperature for 2 h to obtain a 10 wt% sodium citrate aqueous solution. The solution was then ultrasonically degassed for 15 min. A platinum sheet with a length of 6 cm, a width of 2 cm, and a thickness of 1 mm was prepared as the anode material, and a titanium sheet with a length of 6 cm, a width of 2 cm, and a thickness of 1 mm was prepared as the cathode material, serving as the anode and cathode for electrophoretic deposition, respectively. The anode and cathode cells were installed, and a nanodialysis membrane was sandwiched between the two cells. The anode and cathode metal materials were immersed in the anode cell containing the chitosan solution and the cathode cell containing the sodium citrate solution, with an insertion depth of 5 cm and a spacing of 4 cm. A constant voltage DC current was applied, with an electric field strength set to 4 V / cm, for chitosan electrophoretic deposition over a period of 120 min. After deposition, the hydrogel film was removed from the nanodialysis membrane and washed to remove residual ions and unreacted substances, yielding a chitosan hydrogel film with a thickness of 890 μm (see [link to hydrogel film thickness section] for the relationship between deposition time and hydrogel film thickness). Figure 3 The mechanical properties of the thin film are shown in Figure 5 ).
[0068] Example 8
[0069] A method for preparing a hydrogel film on a non-conductive surface includes the following steps:
[0070] 1 g of gelatin powder was dissolved in deionized water and heated and stirred at 60°C for 2 h to completely dissolve the gelatin, yielding a 5 wt% gelatin solution. 30 g of trisodium citrate dihydrate powder was dissolved in deionized water and stirred at room temperature for 2 h to obtain a 30 wt% sodium citrate aqueous solution, which was then ultrasonically degassed for 15 min. A platinum sheet measuring 6 cm in length, 2 cm in width, and 1 mm in thickness was prepared as the anode material, and a titanium sheet measuring 6 cm in length, 2 cm in width, and 1 mm in thickness was prepared as the cathode material, serving as the anode and cathode for electrophoretic deposition, respectively. The anode and cathode cells were installed, with a nanodialysis membrane sandwiched between them. The anode and cathode metal materials were immersed in the anode cell containing the gelatin solution and the cathode cell containing the sodium citrate solution, with an insertion depth of 5 cm and a spacing of 5 cm. A constant voltage DC current was applied, with electric field strengths set to 1 V / cm, 2 V / cm, and 3 V / cm, respectively, for gelatin electrophoretic deposition over a period of 120 min. After deposition, the hydrogel film was removed from the nanodialysis membrane, washed to remove residual ions and unreacted substances, yielding a gelatin hydrogel film (see [link to mechanical properties]). Figure 6 ).
[0071] Comparative Example 1
[0072] 1 g of gelatin powder was dissolved in deionized water and heated and stirred at 60°C for 2 h to completely dissolve the gelatin, yielding a 5 wt% gelatin solution. 30 g of trisodium citrate dihydrate powder was dissolved in deionized water and stirred at room temperature for 2 h to obtain a 30 wt% sodium citrate aqueous solution, which was then ultrasonically degassed for 15 min. The gelatin solution was poured into a mold and refrigerated at 4°C for 12 h to form a pregel. This pregel was then immersed in the sodium citrate aqueous solution for 24 h to obtain a gelatin hydrogel film. The mechanical properties of the obtained film are shown in [reference needed]. Figure 6 .Depend on Figure 6 It can be seen that, compared with traditional methods, the method of the present invention is simpler and more efficient, and the prepared hydrogel film has superior mechanical properties.
[0073] In summary, this invention achieves the directional migration and deposition of polyelectrolyte molecules on the interface of a non-conductive substrate by introducing a hydrophilic non-conductive substrate into an electrolytic cell and applying solutions of different compositions and electric fields on both sides of the substrate. This method fully utilizes the electrophoretic migration characteristics of polyelectrolytes under an electric field, causing them to accumulate and cross-link near the non-conductive substrate, ultimately forming a continuous and stable hydrogel film. Even with a deposition time of only 1 minute, the resulting film still exhibits good uniformity; and even with a deposition time of only 10 minutes, the resulting film still displays excellent mechanical properties. This invention overcomes the dependence of traditional electrodeposition techniques on conductive substrates, providing a universal platform for constructing functional hydrogels on the surfaces of non-conductive materials such as glass and polymer films. Compared with traditional methods, this method offers rapid preparation, simple equipment, and mild operation, and is applicable to various natural and synthetic polyelectrolyte systems, showing great application potential in the field of biomimetic materials preparation.
[0074] The above detailed embodiments describe the implementation of the present invention; however, the present invention is not limited to the specific details described in the above embodiments. Within the scope of the claims and technical concept of the present invention, various simple modifications and changes can be made to the technical solution of the present invention, and these simple modifications all fall within the protection scope of the present invention.
Claims
1. A method for preparing a hydrogel film on a non-conductive surface, characterized in that, Includes the following steps: An electrodeposition cell system comprising a cathode cell and an anode cell was constructed, and a hydrophilic non-conductive substrate was placed between the cathode cell and the anode cell as a deposition carrier for the hydrogel film. An aqueous solution containing polyelectrolytes is injected into the anode cell, and an aqueous solution containing soluble salts is injected into the cathode cell. A DC electric field is applied between the cathode and the anode, causing positively charged polyelectrolyte molecules in the anode cell to undergo electrophoretic migration and accumulate near the interface of the non-conductive substrate, forming a hydrogel film.
2. The method for preparing a hydrogel film on a non-conductive surface according to claim 1, characterized in that, The non-conductive substrate is a non-conductive nanoporous membrane with a pore size of 1-100 nm and a thickness of 10-500 µm.
3. The method for preparing a hydrogel film on a non-conductive surface according to claim 2, characterized in that, The non-conductive nanoporous membrane includes, but is not limited to, one or more of the following: polyvinylidene fluoride membrane, polyamide membrane, cellulose acetate membrane, glass sheet, polyester film, and polypropylene membrane.
4. The method for preparing a hydrogel film on a non-conductive surface according to claim 1, characterized in that, The intensity of the DC electric field is 1-10 V / cm.
5. The method for preparing a hydrogel film on a non-conductive surface according to claim 1, characterized in that, The polyelectrolytes include, but are not limited to, one or more of chitosan, gelatin, and sodium alginate.
6. The method for preparing a hydrogel film on a non-conductive surface according to claim 5, characterized in that, The mass concentration of the polyelectrolyte in the aqueous solution containing the polyelectrolyte is 0.5 wt%-10 wt%.
7. The method for preparing a hydrogel film on a non-conductive surface according to claim 1, characterized in that, The soluble salts include, but are not limited to, sodium chloride and / or sodium citrate.
8. The method for preparing a hydrogel film on a non-conductive surface according to claim 7, characterized in that, The molar concentration of the soluble salt in the aqueous solution containing the soluble salt is 0.001-1.5 mol / L.
9. An electrodeposition apparatus for implementing the method according to any one of claims 1-8, characterized in that, The device includes a cathode pool, an anode pool, and a non-conductive substrate. The anode pool is used to hold an aqueous solution containing a polyelectrolyte and is equipped with an anode. The cathode pool is used to hold an aqueous solution containing soluble salts and is equipped with a cathode. The non-conductive substrate is fixed between the cathode pool and the anode pool to ensure its flatness and liquid isolation. By applying a DC electric field between the cathode and the anode, a hydrogel film can be formed at the interface of the non-conductive substrate.
Citation Information
Patent Citations
Method and device for preparing electro-polymerized silk fibroin hydrogel membrane and application of fibroin hydrogel membrane
CN103981561A